An ethnographic study of outside-circularity and deconstructive creation from the waste reuse practices of the urban waste precariat - Reyneke, Pierre (University of the Witwatersrand, Johannesburg, 2024)
The study consists of an ethnographic inquiry into the waste reuse practices performed by the urban waste precariat on the landfill and streets of Pretoria East, City of Tshwane. I analyse the contribution of this social grouping to the urban circular economy and environment by conceptualising of these waste reuse practices as value-production processes not rooted in capitalism, practised outside of state and formal market recognition and support. I term these forms of existing circularity “outside-circularity” and identify an alternative value-production process termed “deconstructive creation”. The deconstructive creation process produces life from capitalist ruins, an alternative form of value to capitalism. This form of value draws on new formations of kinship and exchanges in a subsidiary and care economy, and functions on principles of everyday communism. Life from the capitalist ruins finds expression in two ways. Firstly, urban life that is more than mere material sustenance is produced, and a form of social solidarity as new kinship formations develop between Zimbabwean migrants in the City of Tshwane. Secondly, urban space is produced in the form of street craft markets and garden beautification to transform the suburban aesthetic. I problematise portrayals of waste reclaimers as an undifferentiated group exclusively performing reclaiming and recycling of paper and packaging materials. For this I develop and apply the social categorisation ‘urban waste precariat’, to move beyond the term ‘reclaimer’ with its singular focus on paper and packaging recycling. The term urban waste precariat incapsulates both recycling and reuse practitioners and hereby, I portray the complexity of the urban waste economy to include waste reuse practices, a cluster of waste work excluded from the literature in South Africa, thus far. Methodologically, I identify points of transition that are seminal to the circularity of the practices seen as meshwork. These points are discard, salvage, disassembly, transformation, exchange, and use. In addition, I trace circuits of material flow, both human and nonhuman, to portray the meshwork that entangles to form waste reuse practices. Through critical ethnography and by viewing waste reuse practices through the concept of skill, I show how space is relationally produced by tracing the socio-spatial history of traditional craft making skill development. The ethnographic data illustrate how this skill is employed in waste reuse practices, from artist hubs in Zimbabwe (Mbare and Chitungwisa) to its emergence through migration in Pretoria East’s informal iii street markets and suburban gardens. The study thus argues for the potential of sustainability and circularity to emerge from such skilled waste reuse practices of deconstructive creation.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; waste reuse; urban waste precariat; deconstructive creation; outside-circularity; City of Tshwane; SDG-4: Quality education